MOLECULAR DYNAMICS STUDY OF OLEIC ACID-BASED SURFACTANTS FOR ENHANCED OIL RECOVERY - Aang Suhendar; Rukman Hertadi; Yani F Alli (Testing Center for Oil and Gas LEMIGAS, 2018)
Surfactants have been intensively used for Enhanced Oil Recovery (EOR). Nevertheless, environmental issues cause some surfactants to become unfavored in EOR application. Biodegradable surfactants are the suitable choice to make the environment safer. However, screening surfactants that have a good performance for EOR are time-consuming and costly. Molecular Dynamics (MD) simulation is an alternative solution to reduce cost and time. In the present study, oleic acid-based surfactants that combined with the various length of polyethylene glycol were studied. The potential surfactants were screened by MD simulation to evaluate their ability to reduce the Interfacial Tension (IFT) between oil and water layers, which is the by GROMACS software with Gromos force field and SPC water model. Carboxyl-terminal of the oleic acid was substituted by a different length of polyethylene glycol. All MD simulations were prepared in octadecane–water mixture with temperature ranges of 303-363 K. Our simulations found that the increasing number of polyethylene glycol was not always followed by the decreasing of IFT value between octadecane and water layers. These results were validated with the experimental data and found the similar IFT profile. The simulation of oil emulsification showed that all surfactant samples have good performance and stability as exhibited by their emulsification rate and emulsion stability in different temperatures. The last test to get the best surfactant was the wetability test. The simulation gave the result that both PEG100-oleic and PEG400-oleic were able to change wetability of rocks from oil-wet to water-wet. Accordingly, PEG400-oleic is the best nonionic surfactant candidate due to its performance in each simulation test.